Pemeriksaan Pajak Dalam Rangka Pengujian Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Jakarta Duren Sawit - Hizkia Adiwiguna; Selvi Selvi (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to analyze how tax inspections in the context of taxpayer compliance testing at Jakarta Small Taxpayers Office of Duren Sawit, to analyze the obstacles of tax inspectors in the tax inspection process in the context of taxpayer compliance testing at Jakarta Small Taxpayers Office of Duren Sawit and to analyze the efforts made in overcoming existing obstacles. This research uses a qualitative approach with observation techniques and interviews with the Head of the Examination, Assessment and Billing Section at Jakarta Small Taxpayers Office of Duren Sawit, academics and taxpayers. The results of this study concluded that tax inspection in the context of taxpayer compliance testing at Jakarta Small Taxpayers Office of Duren Sawit in terms  of taxpayer awareness is  still  relatively very low. In fact, in terms of service, communication and notification at Jakarta Small Taxpayers Office of Duren Sawit is quite clear in providing information to taxpayers.